A clinical index for evaluating and monitoring dental erosion - Larsen IB, Westergaard J, Stoltze K, Larsen AI, Gyntelberg F, Holmstrup P (Blackwell Synergy, 2000)
This study describes a new fine-scaled system for classifying initial and advanced dental erosions. The system includes the use of study casts of the teeth in an epoxy resin with an accurate surface reproduction. The severity of erosion on each tooth surface is scored according to six grades of severity. In addition, the presence of a Class V restoration and dental erosion on the same surface Key words: clinical index; dental erosion; increases the erosion score, as it is assumed that the need for restorative treatment oral epidemiology can be caused by the erosion.